2013
DOI: 10.1111/wvn.12009
|View full text |Cite
|
Sign up to set email alerts
|

Turning Knowledge Into Action at the Point‐of‐Care: The Collective Experience of Nurses Facilitating the Implementation of Evidence‐Based Practice

Abstract: Background: Facilitation is considered a way of enabling clinicians to implement evidence into practice by problem solving and providing support. Practice development is a well-established movement in the United Kingdom that incorporates the use of facilitators, but in Canada, the role is more obtuse. Few investigations have observed the process of facilitation as described by individuals experienced in guideline implementation in North America.AimTo describe the tacit knowledge regarding facilitation embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 29 publications
2
107
0
4
Order By: Relevance
“…An integrative review, case audit and structured interviews, and an international two-day facilitator’s forum were used to delineate key practical and conceptual elements of facilitation as a ‘process beyond an assigned role’ in implementation [11,12,20]. Facilitation is described as a multifaceted process comprising more than 50 specified actions grouped across four stages: planning for change, leading and managing change, monitoring progress and on-going implementation, and evaluating change.…”
Section: Resultsmentioning
confidence: 99%
“…An integrative review, case audit and structured interviews, and an international two-day facilitator’s forum were used to delineate key practical and conceptual elements of facilitation as a ‘process beyond an assigned role’ in implementation [11,12,20]. Facilitation is described as a multifaceted process comprising more than 50 specified actions grouped across four stages: planning for change, leading and managing change, monitoring progress and on-going implementation, and evaluating change.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically with regard to implementation, Aarons, Ehrhart, Farahnak, and Sklar (2014) have described how leaders can utilize Schein’s (2010) embedding mechanisms to bolster the implementation climate in their organizations, and Aarons, Ehrhart, Farahnak, and Hurlburt (2015) describe leadership training specifically targeting improvement in EBP implementation. Research has also shown that development of strategic partnerships, the use of multiple strategies, and facilitator characteristics are associated with successful EBP implementation (Dogherty, Harrison, Graham, Vandyk, & Keeping-Burke, 2013). Future research could analyze the effectiveness of different types of leadership, strategies, and individual characteristic variables that either help to develop, foster, or impede EBP implementation climate.…”
Section: Discussionmentioning
confidence: 99%
“…Still, there is a need for more focus on implementation and probably that need its own intervention. Successful implementation needs more strategies than an educational intervention [24].…”
Section: Lessons Learnedmentioning
confidence: 99%